Effect of steel and PVA fibres as monofibres on strength and cracking properties of fly ash and slag-based alkali-activated concrete - Mangalapuri Venkateswarlu; T. D. Gunneswara Rao (Journal of Engineering and Applied Science, 2023)
Abstract The present paper explores the experimental study on the influence of steel fibres (SF) and polyvinyl alcohol fibres (PVAF) as monofibres on the strength, and cracking properties of alkali-activated concrete with varying ground granulated blast furnace slag (GGBFS) and fly ash amounts was examined under ambient curing in this study. The alkali activator was a mixture of sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) solutions. A molarity of 2 M NaOH solution and a fixed alkaline ratio (AR) of 1.5 were used in all mixes. Steel and polyvinyl alcohol (PVA) fibres were employed as monofibres. Steel fibres were added in 0.5%, 0.75%, and 1.00% volume fractions, whereas PVAF were added in 0.15%, 0.30%, and 0.45% volume fractions. In this study, a compressive strength test was performed; furthermore, a uni-axial tension test on reinforced concrete prisms was performed for tensile (first crack load, yield load, tensile stress in concrete, and tension stiffening effect) and cracking (crack spacing and crack width) properties. From the test results, better improvements in compressive strength, first crack load, yield load, tensile stress in concrete, and tension stiffening effect were observed in specimens having 1.00% steel fibres and specimens having 0.30% PVA fibres as monofibres. In the mixes containing 100% GGBFS, there was an improvement in the first crack load of approximately 46% due to 1.00% steel fibres and an approximately 29% improvement due to 0.30% PVA fibres. Furthermore, reduced crack spacings and minimum crack widths were found at 1.00% volume fraction of steel fibres and also in specimens having 0.30% PVA fibres. Overall, this study found that 1.00% steel and 0.3% PVA fibres as monofibres in fly ash-slag-based alkali-activated concrete (FSAAC) were optimal doses in terms of strength and cracking characteristics.